2013
DOI: 10.3389/fnhum.2013.00191
|View full text |Cite
|
Sign up to set email alerts
|

The role of musical training in emergent and event-based timing

Abstract: Introduction: Musical performance is thought to rely predominantly on event-based timing involving a clock-like neural process and an explicit internal representation of the time interval. Some aspects of musical performance may rely on emergent timing, which is established through the optimization of movement kinematics, and can be maintained without reference to any explicit representation of the time interval. We predicted that musical training would have its largest effect on event-based timing, supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 33 publications
(76 reference statements)
7
37
1
Order By: Relevance
“…Timing ability is measured by analyzing the time series of inter-response intervals (IRIs) of the unpaced phase, such that an IRI is defined by the time interval between adjacent taps. The tapping paradigm employed in the present study was also used in a recent study from our group that showed that musicians are substantially less variable in the timing of their unpaced responses compared to non-musicians (Baer et al, 2013). This is consistent with other studies that have demonstrated that musicians are less variable (Franĕk et al, 1991;Repp, 2010;Repp and Doggett, 2007), and show less drift away from the prescribed tapping rate compared to non-musicians (Collier and Ogden, 2004).…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Timing ability is measured by analyzing the time series of inter-response intervals (IRIs) of the unpaced phase, such that an IRI is defined by the time interval between adjacent taps. The tapping paradigm employed in the present study was also used in a recent study from our group that showed that musicians are substantially less variable in the timing of their unpaced responses compared to non-musicians (Baer et al, 2013). This is consistent with other studies that have demonstrated that musicians are less variable (Franĕk et al, 1991;Repp, 2010;Repp and Doggett, 2007), and show less drift away from the prescribed tapping rate compared to non-musicians (Collier and Ogden, 2004).…”
Section: Introductionsupporting
confidence: 88%
“…Similar factors may be responsible for the volume decreases observed here. In support of this explanation, we found in a previous study that non-musicians exhibited a negative association between movement jerk and timer variability on a tapping task, while musicians' jerk and timing were decoupled, indicating that musicians were able to achieve superior timing with less sensory feedback (Baer et al, 2013), as jerk is a source of proprioceptive information (Balasubramaniam et al, 2004).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations